Percutaneous endoscopic gastrostomy:Indications,technique,complications and management - Rahnemai-Azar, Ata A; Rahnemaiazar, Amir A; Naghshizadian, Rozhin; Kurtz, Amparo; Farkas, Daniel T (World journal of gastroenterology : WJG, 2014)
Percutaneous endoscopic gastrostomy(PEG)is the preferred route of feeding and nutritional support in patients with a functional gastrointestinal system who require long-term enteral nutrition.Besides its wellknown advantages over parenteral nutrition,PEG offers superior access to the gastrointestinal system over surgical methods.Considering that nowadays PEG tube placement is one of the most common endoscopic procedures performed worldwide,knowing its indications and contraindications is of paramount importance in current medicine.PEG tubes are sometimes placed inappropriately in patients unable to tolerate adequate oral intake because of incorrect and unrealistic understanding of their indications and what they can accomplish.Broadly,the two main indications of PEG tube placement are enteral feeding and stomach decompression.On the other hand,distal enteral obstruction,severe uncorrectable coagulopathy and hemodynamic instability constitute the main absolute contraindications for PEG tube placement in hospitalized patients.Although generally considered to be a safe procedure,there is the potential for both minor and major complications.Awareness of these potential complications,as well as understanding routine aftercare of the catheter,can improve the quality of care for patients with a PEG tube.These complications can generally be classified into three major categories:endoscopic technical difficulties,PEG procedure-related complications and late complications associated with PEG tube use and wound care.In this review we describe a variety of minor and major tube-related complications as well as strategies for their management and avoidance.Different methods of percutaneous PEG tube placement into the stomach have been described in the literature with the"pull"technique being the most common method.In the last section of this review,the reader is presented with a brief discussion of these procedures,techniques and related issues.Despite the mentioned PEG tube placement complications,this procedure has gained worldwide popularity as a safe enteral access for nutrition in patients with a functional gastrointestinal system.